Activity enhancement upon the incorporation of titanium: au@ti-sio2 core-shell nanocatalysts for the CO oxidation reaction - Sekhar, Anandakumari C. Sunil; Kottavarithottil Ziyad; Soni, Yogita; Vinod, Chathakudath P. (ChemCatChem, 2015)
The encapsulation of gold nanoparticles 8-12nm in size within a porous Ti-SiO2 shell to form a core-shell nanoarchitecture was investigated, and the catalytic activity of the resulting structure was probed. Detailed characterization of the synthesized materials shows that the core-shell morphology is lost beyond a certain amount of incorporated titanium, and results in normal gold-supported Ti-SiO2. The material has a high surface area (913m(2)g(-1)) and high porosity, both of which make it an excellent choice for catalytic applications. With the optimum amount of incorporated Ti, the core-shell catalyst shows excellent room-temperature CO oxidation activity over several cycles with retention of its morphology at higher temperatures.
Keywords: core-shell structures; gold nanoparticles; Oxidation; Ti-SiO2

Co@CoAl-layered double hydroxide/nitrogen-doped graphene composite catalyst for Al-H2O-based batteries: simultaneous hydrogen production and electricity generation - Nadeema, Ayasha; Pandurang Kharabe, Geeta; Prakash Biswal, Dibya; Kurungot, Sreekumar (ChemElectroChem, 2020)
Currently, the low energy efficiency of water electrolysis has compelled research toward the development of novel and energy-effective strategies for low-cost H-2 generation. In this context, we report a new concept of simultaneous H-2 and electricity generation by separating out the exothermic self-sustained Al-H2O reaction via electrochemistry. In addition, to catalyze the cathodic water reduction reaction, a single-pot and environmentally benign synthesis method is adopted. It results in the design of an electrocatalyst composed of Co@CoAl-layered double hydroxide core-shell nanospheres anchored over in situ generated N-doped graphene. Toward the water reduction reaction, the designed catalyst shows a negative voltage shift of mere around 113 mV with respect to the commercial Pt/C catalyst to reach the benchmark 10 mA cm(-2), with excellent stability of approximately 86 % voltage retention after 12 h of continuous operation. The catalytic superiority of our material is evident when taken for battery-level testing; the fabricated device was able to deliver an average output voltage of around 0.95 V at a discharge current density of 5 mA cm(-2) along with H-2 liberation, which was also detected and quantified through gas chromatography.
Keywords: Al-H2O fuel cells; chronopotentiometry; core-shell structures; hydrogen evolution reaction; layered double hydroxides